2016
DOI: 10.1038/srep27743
|View full text |Cite
|
Sign up to set email alerts
|

High-responsivity vertical-illumination Si/Ge uni-traveling-carrier photodiodes based on silicon-on-insulator substrate

Abstract: Si/Ge uni-traveling carrier photodiodes exhibit higher output current when space-charge effect is overcome and the thermal effects is suppressed. High current is beneficial for increasing the dynamic range of various microwave photonic systems and simplifying high-bit-rate digital receivers in many applications. From the point of view of packaging, detectors with vertical-illumination configuration can be easily handled by pick-and-place tools and are a popular choice for making photo-receiver modules. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…8b shows the calculated impact of the absorber layer doping concentration on the bandwidth of the UTC PD. It has been proposed [19,20] that introducing step-like and gradient doping concentration profiles in the absorber layer lead to a speed up of electron diffusion towards the collector layer by forming a quasi-neutral electric field, which improves carrier transport [3]. Here we compare a constant doping concentration (1 × 10 19 cm −3 ) with graded doping concentrations in the absorber layer of the UTC PD.…”
Section: Absorber Layermentioning
confidence: 99%
“…8b shows the calculated impact of the absorber layer doping concentration on the bandwidth of the UTC PD. It has been proposed [19,20] that introducing step-like and gradient doping concentration profiles in the absorber layer lead to a speed up of electron diffusion towards the collector layer by forming a quasi-neutral electric field, which improves carrier transport [3]. Here we compare a constant doping concentration (1 × 10 19 cm −3 ) with graded doping concentrations in the absorber layer of the UTC PD.…”
Section: Absorber Layermentioning
confidence: 99%
“…In this study, the radiative properties of SOI structures, based on the earlier studies of Ravindra et al 11 on SIMOX (Separation by IMplanted Oxygen) structures, with 200-nm Si/400-nm SiO 2 /Sisubstrate, as the control group, are considered to demonstrate the validity of the proposed simulation model. In Figure 1A, A case study, based on Li et al 12 considering the thickness of Si as 1000 nm on top of a 2000 nm thick SiO 2 , is presented. Another case study is based on Badri et al 13 with the thickness of SiO 2 as 2000 nm with the top layer of Si varying in thickness from 75 to 325nm.…”
Section: Silicon On Insulatormentioning
confidence: 99%
“…The thickness of Ge layer is varied from 400 to1200 nm in steps of 200nm (i.e., 400, 600, 800, 1000, 1200 nm) and the thickness of bulk Si or SOI substrates consisting of thin SiO 2 and silicon layer (150nm Si on 400nm SiO 2 decreasing to 60nm Si on 150nm SiO 2 ) 14 are considered. ' ' ( ) ( ) Besides, another interesting case study, based on Chong et al 12 on coupled waveguides of Ge-on-SOI (Si/Ge/Si/Si/SiO 2 /Si), as shown in Figure 1d, with the thickness of Si (100nm), Ge (1000nm), Si(600 nm), Si(220nm) and SiO 2 (2000nm), respectively, is investigated. Besides the Ge photodetector, we also report the optical properties of Ge x Si 1-x (x = 0.05, 0.1 and 0.15) alloys on Si by varying the thickness of Ge x Si 1-x from 100-1000 nm based on the case study of Kadri et al 15 The simulations are implemented in MATLAB using fitting parameters based on Forouhi-Bloomer dispersion model for the n and k of Si, Ge, SiGe and SiO 2 , as shown in Table 1.…”
Section: Ge-on-si Photodetectorsmentioning
confidence: 99%
“…The existence of a depletion region -created by application of a reverse bias to the junction -results in a low dark current value [37]. Still, this structure is not optimal from the point of view of carrier extraction speed since a bulk charge appearing due the difference in mobility of electrons and holes limits the detector bandwidth [38], [39]. The latter is addressed by UTC (Uni-Traveling-Carrier) photodiodes that use heterostructures to make only electrons contribute to the signal current [38]- [41].…”
Section: A Semiconductor Absorber Type Photodetectorsmentioning
confidence: 99%